Makna Perubahan Digital Creative Center (DCC) Berganti Nama Digital Creative Community (DICO) - Tsabit, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The creative industry has grown rapidly and dynamically. With the rise of digital technology in Indonesia, many start-up companies have emerged, especially in the creative industry. An attractive company name is a selling point to win the competition. In a company there is a name that will grow or the perception of a brand. One of the keys to the success or failure of a company is the name. Name changes must also be accompanied by rebranding. The method used is a descriptive method that aims to explain factually and accurately. Data collection techniques are carried out through interviews, the results of this study were analyzed using descriptive analysis techniques. in the name transformation, there is also an implied meaning to show innovation and stability, and reflect the exclusive values that are carried. The results of the study show that. The company name is very influential. The conclusion of this study is that in general the company name follows the current trend.